Chronic lymphocele after modified radical mastectomy – treatment - Morawiec, Zbigniew; Stańczyk, Maciej; Howaniec, Józef; Pawlak, Mariusz; Kołacińska, Agnieszka; Rajchert, Łukasz; Tazbir, Marek; Galicki, Michał (Menopause Review/Przegląd Menopauzalny, 2007)
Lymphocele is the most common complication of breast cancer surgery. Although its pathophysiology remains unknown, the prognosis and outcome are favourable. We report an incidence of chronic and persistent lymphocele still present 29 months after radical mastectomy in a 70-year old woman consulted in our outpatient department. Ultrasonography revealed a large fluid retention area of 12 cm in diameter extending from the left axilla to the left midclavicular lane. The patient refused surgical resection so puncture drainage and local injections of vibramycine into the cyst were performed once a month and partial regression was observed. Hyperlipidaemia and infection in perioperative period as possible causes of chronic lymphocele are discussed.